Toothbrushing: to the best of ones abilities is possibly not good enough - Deinzer, Renate; Ebel, Stefanie; Blättermann, Helen; Weik, Ulrike; Margraf-Stiksrud, Jutta; Justus Liebig University Giessen (My University, 2018)
BACKGROUND: Weaknesses in toothbrushing performance can be seen when young adults are instructed to perform habitual toothbrushing. Nothing is known about toothbrushing behavior when instructed to perform to the best abilities. The present study analyzes such behavior and compares it to habitual behavior.METHODS: A random sample of N = 98 young adults born in 1995 was examined in 2014/2015.They were asked to perform oral hygiene to the best of their abilities in front of a camera. Videos were analyzed regarding details of brushing behavior. A quality index was developed which describes the extent of the neglect of brushing on palatinal and vestibular surfaces. Data were compared to those of an earlier study of young adults (born in 1992, examined in 2011, N = 101) who were asked to perform oral hygiene as they habitually do.RESULTS: The 1995 cohort (best abilities) brushed their teeth significantly longer than the 1992 cohort (habitual brushing). This was due to significant longer brushing at vestibular and occlusal surfaces. Neglect of palatinal surfaces was similar in both cohorts. Groups did not differ regarding brushing movements. 40% of the brushing time on lateral surfaces was spent with scrubbing movements despite opposing advice in common oral hygiene instructions.CONCLUSIONS: Toothbrushing to the best of one´s abilities might still not be good enough. Young adults apparently lack a reasonable concept of what is meant by high quality toothbrushing. More efforts should thus be undertaken to explain them (and adults) this concept.
Keywords: oral hygiene; community dentistry; dental education; dental hygiene; preventive dentistry; ddc:610